Talent turnover and retention research: The case of tourism sector organisations in Saudi Arabia. Issue 2 (10th May 2018) - Alferaih, Adel; Sarwar, Shagufta; Eid, Ayman
Abstract : Purpose: The purpose of this paper is to understand the direct impact of some of the salient factors from the talent management (TM) literature (role conflict, extrinsic rewards, and job satisfaction) and the indirect impact of other factors (organisational commitment, talent retention, and talent engagement) on talent turnover intention. Design/methodology/approach: A survey questionnaire collected 521 valid responses from employees holding managerial and non-managerial positions at various levels in 54 five-star hotels in 6 cities in Saudi Arabia. Findings: Significant support was found for all nine hypotheses formulated to test the relationships among the seven constructs above. The model was found to explain 68 per cent of variance in talent turnover intention. Research limitations/implications: The study contributes to human resource management literature in general and TM in particular by examining the different constructs used in the TM models and by conceptualising a research model, which was empirically validated within the service sector in the context of Saudi Arabia. Practical implications: The research has several implications for practitioners in the tourism/service sector in the Middle East, pertaining to the management of talented employees. Specifically, it recommends that managers should promote training and development scenarios and provide a better work environment to strengthen individuals' commitment to their jobs. Originality/value: This is one of the first studies to examine a comprehensive model of TM in the Arab world in general and in Saudi Arabia in particular, using data gathered from employees in the tourism sector.